The Effect of Communicative Language Teaching on Kurdish EFL Learners' Speaking Skills in Soran Independent Administration - Ghafar, Zanyar; Akam Azad MOHAMEDAMIN; Vina Fryad MAMND; Exlas Mustafa JUMAA (RADINKA JAYA UTAMA PUBLISHER, 2025)
This study investigates the effect of Communicative Language Teaching (CLT) on the speaking skills of Kurdish EFL learners in the Soran Independent Administration. A quantitative research design was employed, which involved two groups of 7th-grade students, which consisted of 53 students from Dilara Secondary School and Hawdian Secondary School. The data were collected through a questionnaire that consisted of 8 items. The results indicated a significant improvement in students’ performances after attending CLT sessions. The results showed that the student outperformed in fluency over accuracy, and their grammar, pronunciation, and vocabulary expanded. They showed that CLT classes are engaging, the tasks are more real-world, and the classes are more student-centered. Thus, they demonstrated the effectiveness of CLT in promoting real-world communicative competence among young EFL learners in school settings.